REPOSITIONING THE ROLE OF PUBLIC PROSECUTORS AS DOMINUS LITIS IN CORRUPTION CASES: AN ECONOMIC ANALYSIS OF LAW IN GOVERNMENT PROCUREMENT: - Raden Nanda Setiawan; Reda Manthovani; Agus Surono; Andi Wahyu Wibisana (Focus Journal : Law Review, 2025)
This study aims to examine the urgency and potential of applying the Economic Analysis of Law Principle by the State Attorney of Indonesia in its capacity as Dominus Litis in handling corruption cases, in this case in the Government Procurement sector. This study aims to determine the policy related to the authority of the State Attorney as Dominus Litis in handling corruption cases in government procurement. This research is a normative legal study, as well as a case approach using illustrations of corruption cases related to government procurement of goods and services. This approach aims to build the author's legal argument through a review of cases related to the issues to be examined in this paper. Therefore, this research uses a descriptive approach in the form of prescriptive research. The results of this study are the existing conditions of the role of the Public Prosecutor as Dominus Litis to be applied in handling corruption cases in government procurement of goods and services, because the Public Prosecutor has been ineffective in considering the economic value of a prosecution policy. The repositioning of the role of the Public Prosecutor is necessary so that they do not only focus on formal and material evidence, but also consider the social and economic costs. The implications of the Economic Analysis of Law approach reveal that efforts to recover state losses and long-term prevention are more important than current criminalization.